Air Force One : a novel - Collins, Max Allan (New York : Ballantine Books, 1997)
"Terrorists have seized Air Force One thirty thousand feet above the earth. The president, the first lady, their thirteen-year-old daughter, and more than fifty innocent people are on board. The terrorists threaten to execute a hostage every thirty minutes if their demands are not met. The official word from Washington : no negotiations. Time is running out..."--Cover.
National College of Business and Arts
Keywords: Air Force One (Presidential aircraft) -- Fiction; Fiction